The Influence of Investment Returns, Growth Opportunities, Asset Structure on Stock Returns With Capital Structure As An Intervening Variable In Food & Beverage Sector Companies - Tetty Tiurma Uli Sipahutar; Felix Thangdinata; Suryani; Renny Maisyarah (Britain International for Academic Research (BIAR) Publisher, 2024)
This research aims to examine the influence of investment returns, growth opportunities, asset structure on stock returns with capital structure as an intervening variable in food & beverage sector companies.This research uses a quantitative type of research.The population in this research involved 40 food & beverage companies registered on the IDX in the 2018-2021 period. The sample was 13 companies. The data analysis method used is path analysis. The results of the research are that ROI-Return on Investment has no significant effect on stock returns in Food & Beverage Sector Companies. AG-Asset Growth has no significant effect on stock returns in Food & Beverage Sector Companies. FAR-Fixed Asset Ratio does not have a significant effect on stock returns in Food & Beverage Sector Companies.Return on Investmenthas a negative influence on stock returns throughdebt to equityIn Food & Beverage Sector Companies.Growth Opportunitieshas a negative influence on stock returns throughdebt to equityIn Food & Beverage Sector Companies.Asset Structurehas a negative influence on stock returns throughdebt to equityIn Food & Beverage Sector Companies.